Ni / CeO2 nanowire catalyst prepared by one-pot method and preparation method thereof
The preparation of Ni/CeO2 nanowire catalysts by one-pot method solves the problems of complexity and insufficient activity of traditional methods, and achieves the preparation of high yield, uniform nickel distribution and high activity catalysts, which are suitable for industrial applications.
Patent Information
- Application Number
- CN202411394754.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-08
- Publication Date
- 2025-04-08
AI Technical Summary
The preparation method of traditional Ni/CeO2 nanowire catalysts is complex and has many steps, which leads to insufficient activity, poor stability and complex preparation process, limiting its widespread adoption in industrial applications.
The Ni/CeO2 nanowire catalyst was prepared by a one-pot method, which included dissolving the cerium salt and nickel salt in water, quickly adding alkali, and directly transferring the mixture to a hydrothermal kettle without stirring, heating and hydrothermal treatment, followed by suction filtration and drying to obtain the target product Ni/CeO2 nanowire.
A simplified process for preparing Ni/CeO2 nanowire catalyst is realized, with high yield, obvious nanowire characteristics, and uniform distribution of nickel elements. It is suitable as a nickel-based catalyst for water-gas transformation reactions and has high activity and stability.
Smart Images

Figure CN119771422A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of nanomaterials and catalysis, and in particular to a Ni / CeO2 nanowire catalyst prepared by a one-pot method and a preparation method thereof. Background Art
[0002] Under the challenges of environmental pollution and energy crisis facing the world, catalytic technology plays a vital role in reducing pollutant emissions and improving energy efficiency. Cerium dioxide (CeO2) has attracted extensive attention in the fields of automobile exhaust purification, industrial waste gas treatment and chemical synthesis due to its advantages such as high oxygen storage capacity, good thermal stability and excellent catalytic activity. In particular, cerium dioxide nanowires show better catalytic performance due to their high specific surface area and enhanced electron mobility. These characteristics not only increase the active sites, but also improve the catalytic efficiency. Patent CN116969498A discloses a method for preparing ultrafine cerium dioxide nanowires, which successfully synthesizes ultrafine cerium dioxide nanowires by using cerium acetate and sodium hydroxide, through hydrothermal treatment and freeze-drying steps. Similarly, patent CN107814406A uses cerium acetate as a cerium source and ammonia water as a precipitant, and obtains cerium dioxide nanowires through hydrothermal treatment and drying. Cerium dioxide (CeO2) is usually only used as a carrier material and does not have significant catalytic activity itself. Therefore, active metal components need to be introduced to enhance the catalytic performance. In this context, nickel (Ni) is introduced into ceria to form a ceria-supported nickel-based catalyst. This catalyst utilizes the active sites at the Ni-CeO2 interface and significantly improves the catalyst performance through the synergistic effect between the interfaces. In key catalytic reactions such as the treatment of volatile organic compounds (VOCs), the oxidation of carbon monoxide (CO), and water-gas shift, Ni / CeO2 catalysts have shown excellent activity and selectivity, demonstrating their potential for application in industrial catalytic processes.
[0003] When nanowires are used as carriers, the catalytic performance of the catalyst is significantly improved, making Ni / CeO2 nanowire catalysts attract widespread attention in the field of catalysis. Although Ni / CeO2 nanowire catalysts show great potential, the traditional preparation method usually involves preparing cerium dioxide nanowires first, followed by loading and calcination, which bring a series of limitations. For example, problems such as insufficient activity, poor stability and complexity of the preparation process limit its widespread adoption in industrial applications. Patent CN113351211A first prepares nickel particles by organic pyrolysis, disperses them in a spinning precursor solution containing cerium salt, and then prepares fibrous cerium dioxide by electrospinning technology. After subsequent steps such as high-temperature calcination, impregnation and drying, a Ni / CeO2 nanowire catalyst is obtained. This synthesis process is complicated, and electrospinning technology is difficult to expand to industrial-scale production, limiting its industrial application. Patent CN104841443A discloses an innovative method for preparing nanorod-shaped cerium dioxide-nickel oxide composite oxides. This technology uses cerium salt and nickel salt as raw materials, adds a precipitant, performs hydrothermal treatment, dries and calcines, and finally obtains nanorod-shaped cerium dioxide-nickel oxide composite oxide. Compared with the existing methods for preparing Ni / CeO2 nanowires or nanorods, this method is simple to operate and easy to control, and has obvious advantages. However, this method produces rod-shaped cerium dioxide rather than nanowires. In addition, the process includes a calcination step, which may increase the complexity and energy consumption of the preparation process. Therefore, exploring a simplified, efficient and easy-to-scale method for preparing Ni / CeO2 nanowires is of great significance for promoting its large-scale application in actual industry. Summary of the invention
[0004] The purpose of the present invention is to provide a Ni / CeO2 nanowire catalyst prepared by a one-pot method and a preparation method thereof, so as to solve the technical problems existing in the background technology.
[0005] The solution of the present invention to solve the technical problem is:
[0006] The present invention provides a one-pot method for preparing a Ni / CeO2 nanowire catalyst, comprising the following steps:
[0007] Dissolve cerium salt and nickel salt in water, quickly add alkali, transfer the mixture directly to a hydrothermal kettle without stirring, heat it for hydrothermal treatment, filter and dry the hydrothermal product after a period of time to obtain the target product Ni / CeO2 nanowires.
[0008] Preferably, the cerium salt is at least one of cerium nitrate, cerium sulfate, cerium chloride and ammonium cerium nitrate.
[0009] Preferably, the nickel salt is selected from at least one of nickel nitrate, nickel chloride, nickel sulfate and nickel acetate.
[0010] Preferably, the molar ratio of the cerium salt to the nickel salt is 1:(0.01-0.3).
[0011] Preferably, the base is at least one of sodium hydroxide and potassium hydroxide.
[0012] Preferably, the total molar ratio of the cerium salt and the nickel salt to the base is 1:(1-100).
[0013] Preferably, the alkali is added quickly.
[0014] Preferably, after adding the alkali, no stirring is required.
[0015] Preferably, the hydrothermal treatment temperature is (60-120)°C.
[0016] Preferably, the hydrothermal treatment time is (1 to 24) hours.
[0017] Preferably, the drying temperature is (30-60)°C.
[0018] Ni / CeO2 catalysts are widely used in reactions such as volatile organic compound (VOCs) treatment, carbon monoxide (CO) oxidation, and water-gas shift. The Ni / CeO2 nanowire catalyst prepared by the present invention can serve as a catalyst for these reactions. In particular, the nanowire catalyst has a uniform morphology and an aspect ratio of more than 100, which can give full play to the advantages of CeO2 nanowires as a carrier. In addition, the nickel in the catalyst is evenly distributed on the CeO2 nanowires, has the characteristics of an excellent catalyst, and is extremely suitable as a nickel-based catalyst.
[0019] The present invention has the following beneficial effects:
[0020] 1. The raw materials for preparing the Ni / CeO2 nanowire catalyst of the present invention are cheap and readily available, the reaction conditions are mild, and it can be synthesized in one pot without much subsequent treatment. The preparation process is simple, suitable for large-scale production, and has broad prospects for industrial application.
[0021] 2. The Ni / CeO2 nanowire catalyst prepared by the present invention has a high yield.
[0022] 3. The Ni / CeO2 nanowire catalyst prepared by the present invention has obvious nanowire characteristics, and the aspect ratio is greater than 100, which can give full play to the advantages of CeO2 nanowires as a carrier.
[0023] 4. In the Ni / CeO2 nanowire catalyst prepared by the present invention, the nickel element is evenly distributed on the CeO2 nanowire, has the characteristics of an excellent catalyst, and is extremely suitable as a nickel-based catalyst.
[0024] 5. The Ni / CeO2 nanowire catalyst prepared by the present invention is used for water-gas shift reaction and has high activity and stability. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 is the XRD spectrum of Ni / CeO2 nanowires and CeO2 nanorods in Example 1;
[0026] Figure 2 is a scanning electron microscope image of CeO2 nanorods in Example 1;
[0027] Figure 3 This is a scanning electron microscope image of the Ni / CeO2 nanowires in Example 1;
[0028] Figure 4 This is a transmission electron microscopy image of the Ni / CeO2 nanowires in Example 1;
[0029] Figure 5 This is a surface scanning analysis diagram of the Ni / CeO2 nanowires in Example 1;
[0030] Figure 6 The catalytic activity of Ni / CeO2 nanowires in Example 1 in the water-gas shift reaction; Figure 7 XRD spectra of the products treated with hydrothermal treatment at different temperatures in Example 1; DETAILED DESCRIPTION
[0031] In order to make the technical problems, technical solutions and beneficial effects to be solved by the present invention clearer and more understandable, the technical solutions in the embodiments of the present invention are clearly and completely described in combination with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0032] The invention provides a one-pot method for preparing a Ni / CeO2 nanowire catalyst, comprising the following steps: dissolving a cerium salt and a nickel salt in water, quickly adding an alkali without stirring, directly transferring the mixture to a hydrothermal kettle, heating for hydrothermal treatment, filtering and drying the hydrothermal product after a period of time to obtain the target product Ni / CeO2 nanowire.
[0033] According to an embodiment of the present invention, the cerium salt is at least one of cerium nitrate, cerium sulfate, cerium chloride and ammonium cerium nitrate.
[0034] According to an embodiment of the present invention, the nickel salt is selected from at least one of nickel nitrate, nickel chloride, nickel sulfate and nickel acetate.
[0035] According to an embodiment of the present invention, the molar ratio of the cerium salt to the nickel salt is 1:(0.01-0.3).
[0036] According to an embodiment of the present invention, the alkali is at least one of sodium hydroxide and potassium hydroxide.
[0037] According to an embodiment of the present invention, the total molar ratio of the cerium salt and the nickel salt to the base is 1:(1-100).
[0038] According to an embodiment of the present invention, the alkali is added in a rapid manner.
[0039] According to an embodiment of the present invention, after adding the alkali, stirring is not required.
[0040] According to an embodiment of the present invention, the hydrothermal treatment temperature is (60-120)°C.
[0041] According to an embodiment of the present invention, the hydrothermal treatment time is (1 to 24) hours.
[0042] According to the embodiment of the present invention, the drying temperature is (30-60)°C
[0043] The present invention also provides an application of the above catalyst, which is applied to the water-gas shift reaction. The method comprises the following steps: adding a catalyst to a fixed bed reactor, introducing hydrogen, and performing pre-reduction for 2 hours at different temperatures (400°C / 600°C). After the temperature drops to room temperature, CO, H2O and balance gas N2 are introduced into the catalyst, the gas pressure is 0.1MPa, the gas content is kept constant (2% CO-10.7% H2O-87.3N2), and the catalyst space velocity is controlled to be 80000h -1 , water-gas shift reaction was carried out at different temperatures and detected by online chromatography.
[0044] Example 1
[0045] S1: Dissolve cerium nitrate and nickel nitrate in water, the molar ratio of cerium nitrate to nickel nitrate is 0.95:0.05, add sodium hydroxide aqueous solution (1 mol / L), control the molar ratio of metal salt to sodium hydroxide to be 1:3, at this time, there is a precipitate, it must be noted that the whole process does not need to be stirred, transfer the precipitate to the hydrothermal kettle, put it in an oven at 100°C, and hydrothermally treat for 6 hours. After the temperature of the reactor drops to room temperature, the hydrothermal product is filtered, and some deionized water is added to the filter cake during the filtration process to remove the residual ions attached to the filter cake. It is vacuum dried at 50°C for 12 hours to obtain the target product Ni / CeO2 nanowires (referred to as Ni / CeO2 NW-80). We also prepared the hydrothermal product when the molar ratio of cerium nitrate to nickel nitrate became 1:0 (the other synthetic conditions did not change), and the product was CeO2 nanorods (referred to as CeO2 NR-80).
[0046] The phases of the Ni / CeO2 NW-80 and CeO2NR-80 samples involved in the present invention were confirmed by X-ray diffraction (XRD) analysis. Figure 1 The XRD spectra of Ni / CeO2 NW-80 and CeO2 NR-80 are shown in Figure 2. The analysis results show that the XRD spectrum of the Ni / CeO2 NW-80 sample is consistent with the standard card of pure CeO2 (JCPDS: 34-0394), and no characteristic peaks of nickel and its oxides or hydroxides are observed, thus confirming that the phase of Ni / CeO2 NW-80 is CeO2. Similarly, the XRD spectrum of CeO2 NR-80 also confirms that its phase is CeO2 (JCPDS: 34-0394).
[0047] The morphology of Ni / CeO2 NW-80 and CeO2 NR-80 was observed by scanning electron microscopy (SEM). Figure 2 and Figure 3 The SEM images of CeO2 NR-80 and Ni / CeO2 NW-80 are shown in Figure 1. The SEM image of CeO2 NR-80 shows that the sample is rod-shaped with an aspect ratio of about 25. The SEM image of Ni / CeO2 NW-80 clearly shows that the catalyst has the morphology of nanowires with an aspect ratio of more than 100, which is significantly higher than that of CeO2NR-80. We also used transmission electron microscopy (TEM) to observe the fine structure of CeO2 NW-80 in detail. Figure 4 The TEM image of CeO2 NW-80 shows that CeO2 NW-80 is a nanowire with a diameter of about 20 nm, which has obvious characteristics of linear nanomaterials. The element distribution of CeO2 NW-80 was analyzed by energy dispersive X-ray diffraction (EDX). Figure 5 The EDX surface scanning analysis diagram of CeO2 NW-80 shows that the nickel element is evenly distributed on the nanowires. Combining the SEM and TEM images, XRD spectra and EDX surface scanning analysis diagram of CeO2 NW-80, we confirmed that the Ni / CeO2 nanowire catalyst prepared by the one-pot method of the present invention has obvious linear characteristics, its physical phase is CeO2, and the nickel element is evenly distributed on the CeO2 nanowires, showing excellent structural characteristics and potential catalytic application prospects.
[0048] S2: Take 50mg CeO2 NW-80 catalyst and load it into the reaction tube of the fixed bed reactor, introduce hydrogen, and reduce the catalyst at 400℃ / 600℃ for 2h. When the temperature in the reaction tube drops to room temperature, switch the reducing gas to the reaction gas (2% CO-10.7% H2O-87.3N2), the gas pressure is 0.1MPa, keep a constant flow rate, and control the reaction time and space velocity to 80000h-1 At room temperature, the sample was purged with the reaction gas for 30 minutes to discharge the hydrogen in the reaction tube. The reaction temperature started from room temperature, and the residence time at each temperature point should be greater than 2 hours to ensure that the catalytic activity of the catalyst can remain stable at this temperature, and the conversion rate of CO in the water gas shift reaction was detected by online chromatography.
[0049] We compared the effects of different reduction temperatures on the catalytic activity of CeO2 NW-80. At the same time, in order to fully evaluate the performance of the catalyst of the present invention, we also prepared Ce according to the method reported in the literature Applied Catalysis B: Environmental, 2000 (27), 179-191. 0.85 Ni 0.05 La 0.1 O x The catalyst was used as a reference. It should be noted that the catalyst exhibited ultrahigh activity in the water-gas shift reaction and was at the leading level among many cerium dioxide-supported nickel-based catalysts reported in existing literature. Figure 6 shown. Figure 6 The figure shows the catalytic activity of each catalyst in the water-gas shift reaction. From the figure, we can see that the unreduced CeO2 NW-80 catalyst shows almost no catalytic activity. As the reduction temperature increases, its catalytic activity gradually increases. By comparison, the activity of the catalyst reduced at 600℃ is better than that at 400℃. The CeO2 NW-80 catalyst reduced at 600℃ shows the same catalytic activity as Ce 0.85 Ni 0.05 La 0.1 O x The catalytic activity of CeO2 NW-80 catalyst is similar to that of CeO2 NW-80 catalyst, although slightly lower than that of CeO2 NW-80 catalyst. Under the same reaction conditions, the temperature at which CeO2 NW-80 catalyst achieves complete CO conversion is 420℃. 0.85 Ni 0.05 La 0.1 O x The conversion temperature of the catalyst is 400°C. Further observations show that at a reaction temperature of 420°C, C e0.85 Ni 0.05 La 0.1 O x The activity of the catalyst began to decline, indicating that its activity stability in the high temperature region was insufficient. However, the CeO2 NW-80 catalyst maintained stable activity even under high temperature conditions, showing better thermal stability. This feature is extremely beneficial for the widespread promotion of the CeO2 NW-80 catalyst in industrial applications.
[0050] Example 2
[0051] Dissolve cerium nitrate and nickel nitrate in water, the molar ratio of cerium nitrate to nickel nitrate is 0.95:0.05, add an aqueous solution of sodium hydroxide (1 mol / L), control the molar ratio of metal salt and sodium hydroxide to be 1:3, and a precipitate is produced at this time. It must be noted that the whole process does not require stirring. Transfer the precipitate to a hydrothermal kettle and put it into an oven at different temperatures (80°C, 100°C, 120°C) for hydrothermal treatment for 6 hours. After the temperature of the reactor drops to room temperature, filter the hydrothermal product. Add some deionized water to the filter cake during the filtration process to remove residual ions attached to the filter cake. Vacuum dry at 50°C for 12 hours to obtain the target product Ni / CeO2 nanowires. The XRD spectrum of the obtained product is shown as follows: Figure 7 As shown in the figure, we can see that the phases of the samples hydrothermally treated at 80℃, 100℃, and 120℃ are all CeO2(34-0394).
[0052] Example 3
[0053] Cerium nitrate, cerium sulfate, ammonium cerium nitrate and cerium chloride were used as cerium salts. Cerium salt and nickel nitrate were dissolved in water. The molar ratio of cerium salt and nickel nitrate was 0.95:0.05. An aqueous solution of sodium hydroxide (1 mol / L) was added to control the molar ratio of metal salt and sodium hydroxide to be 1:3. At this time, precipitation was produced. It must be noted that the whole process does not require stirring. The precipitate was transferred to a hydrothermal kettle and placed in an oven at 100°C for hydrothermal treatment for 6 hours. After the temperature of the reactor dropped to room temperature, the hydrothermal product was filtered. During the filtration process, some deionized water was added to the filter cake to remove the residual ions attached to the filter cake. The target product Ni / CeO2 nanowires were obtained by vacuum drying at 50°C for 12 hours. Table 1 is a comparison of the yield of Ni / CeO2 nanowires prepared using different cerium salts. As can be seen from the table, the obtained products are all CeO2, and the yield is greater than 70%. Among them, the sample using cerium nitrate has the highest yield, up to 91.6%.
[0054] Table 1 Comparison of the yield of Ni / CeO2 nanowires prepared using different cerium salts
[0055] Experimental Group raw material product Yield 1 Cerium nitrate <![CDATA[CeO2]]> 91.6% 2 Cerium Sulfate <![CDATA[CeO2]]> 79.4% 3 Cerium ammonium nitrate <![CDATA[CeO2]]> 72.3% 4 Cerium chloride <![CDATA[CeO2]]> 84.7%
[0056] Example 4
[0057] Using different nickel salts, cerium nitrate, nickel nitrate, nickel sulfate, nickel chloride and nickel acetate were dissolved in water. The molar ratio of cerium nitrate to nickel salt was 0.95:0.05. An aqueous solution of sodium hydroxide (1 mol / L) was added to control the molar ratio of metal salt to sodium hydroxide to be 1:3. At this time, a precipitate was produced. It must be noted that the whole process does not require stirring. The precipitate was transferred to a hydrothermal kettle and placed in an oven at 100°C for hydrothermal treatment for 6 hours. After the temperature of the reactor dropped to room temperature, the hydrothermal product was filtered. During the filtration process, some deionized water was added to the filter cake to remove the residual ions attached to the filter cake. The target product was obtained by vacuum drying at 50°C for 12 hours. Table 2 is a comparison of the yield of Ni / CeO2 nanowires prepared using different nickel salts. As can be seen from the table, the obtained products are all CeO2. The yields of Ni / CeO2 nanowires were all greater than 80% when nickel nitrate, nickel sulfate, nickel chloride and nickel acetate were used as raw materials, namely 91.6%, 89.3%, 82.4% and 87.4% respectively. It can be seen that the effect of nickel salt changes on the yield is significantly smaller than that of cerium salts.
[0058] Table 2 Yield of Ni / CeO2 nanowires prepared using different nickel salts
[0059] Experimental Group raw material product Yield 1 Nickel nitrate <![CDATA[CeO2]]> 91.6% 2 Nickel sulfate <![CDATA[CeO2]]> 89.3% 3 Nickel chloride <![CDATA[CeO2]]> 82.4% 4 Nickel acetate <![CDATA[CeO2]]> 87.4%
[0060] Example 5
[0061] Dissolve cerium nitrate and nickel nitrate in water, the molar ratio of cerium nitrate to nickel salt is 0.95:0.05, add sodium hydroxide aqueous solution (1mol / L), control the molar ratio of metal salt to sodium hydroxide to be 1:3, and precipitate is produced at this time. It must be noted that the whole process does not need to be stirred. Transfer the precipitate to the hydrothermal kettle and put it into a 100℃ oven to adjust the hydrothermal treatment time (1h, 6h, 24h, 36h and 48h). After the temperature of the reactor drops to room temperature, the hydrothermal product is filtered. During the filtration process, some deionized water is added to the filter cake to remove the residual ions attached to the filter cake. The target product is vacuum dried at 50℃ for 12h to obtain the target product. Table 3 shows the effect of different hydrothermal treatment times on the product morphology. From the table, we can see that the hydrothermal treatment time has no effect on the physical phase of the product, all of which are CeO2. But it has an effect on the morphology of the product. When the hydrothermal treatment time is greater than 24h, the product obtained is no longer a nanowire but a nanorod.
[0062] Table 3 shows the effect of different hydrothermal treatment time on product morphology
[0063] Experimental Group time product Morphology 1 1h <![CDATA[CeO2]]> Nanowires 2 6h <![CDATA[CeO2]]> Nanowires 3 24h <![CDATA[CeO2]]> Nanowires 4 36h <![CDATA[CeO2]]> Nanorods 5 48h <![CDATA[CeO2]]> Nanorods
[0064] Example 6
[0065] Dissolve cerium nitrate and nickel nitrate in water, change the molar ratio of cerium nitrate and nickel nitrate to (0.99:0.01, 0.95:0.05, 0.90:0.1, 0.85:0.15 and 0.7:0.30), add an aqueous solution of sodium hydroxide (1 mol / L), control the molar ratio of metal salt and sodium hydroxide to 1:3, and precipitate is produced at this time. It must be noted that the whole process does not need to be stirred. Transfer the precipitate to the hydrothermal kettle, put it in an oven at 100°C, and hydrothermally treat it for 6 hours. After the temperature of the reactor drops to room temperature, the hydrothermal product is filtered, and some deionized water is added to the filter cake during the filtration process to remove the residual ions attached to the filter cake. It is vacuum dried at 50°C for 12 hours to obtain the target product. Table 4 shows the effect of different molar ratios of cerium nitrate and nickel nitrate on the product phase. From the table, we can see that when the proportion of nickel nitrate is greater than 10%, the nickel oxide phase will appear in the hydrothermal product.
[0066] Table 4 Effect of different molar ratios of cerium nitrate and nickel nitrate on product phase
[0067] Experimental Group Molar Ratio phase of matter 1 0.99:0.01 <![CDATA[CeO2]]> 2 095:0.05 <![CDATA[CeO2]]> 3 0.90:0.1 <![CDATA[CeO2]]> 4 0.85:0.15 <![CDATA[CeO2、NiO]]> 5 0.7:0.30 <![CDATA[CeO2、NiO]]>
[0068] Example 7
[0069] Dissolve cerium nitrate and nickel nitrate in water, the molar ratio of cerium nitrate to nickel salt is 0.95:0.05, add an aqueous solution of sodium hydroxide (1 mol / L), control the molar ratio of metal salt to sodium hydroxide to be 1:3, and a precipitate is produced at this time. It must be noted that the whole process does not require stirring. The precipitate is transferred to a hydrothermal kettle and placed in an oven at 100°C for 6 hours of hydrothermal treatment. After the temperature of the reactor drops to room temperature, the hydrothermal product is filtered. During the filtration process, some deionized water is added to the filter cake to remove residual ions attached to the filter cake. The target product is vacuum dried at different temperatures for 12 hours (30°C, 50°C, 100°C and 150°C) to obtain the target product. Table 5 shows the effect of different drying temperatures on the product morphology. As can be seen from the table, the drying temperature has no effect on the physical phase of the product, all of which are CeO2, but it has a huge impact on the product morphology. The product obtained after the drying temperature is greater than 50°C is no longer a nanowire.
[0070] Table 5 shows the effect of different drying temperatures on product morphology
[0071] Experimental Group time product Morphology 1 30℃ <![CDATA[CeO2]]> Nanowires 2 50℃ <![CDATA[CeO2]]> Nanowires 3 100℃ <![CDATA[CeO2]]> Nanorods 4 150℃ <![CDATA[CeO2]]> Nanorods
[0072] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device.
[0073] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A one-pot method for preparing Ni / CeO2 nanowire catalyst, characterized in that: The following steps are involved: Dissolve cerium salt and nickel salt in water, quickly add alkali, transfer the mixture directly to a hydrothermal kettle without stirring, heat it for hydrothermal treatment, and after a period of time, filter and dry the hydrothermal product to obtain the target product Ni / CeO2 nanowires.
2. The preparation method according to claim 1, characterized in that: The cerium salt is selected from at least one of cerium nitrate, cerium sulfate, cerium chloride and ammonium cerium nitrate.
3. The preparation method according to claim 1, characterized in that: The nickel salt is selected from at least one of nickel nitrate, nickel chloride, nickel sulfate and nickel acetate.
4. The preparation method according to claim 1, characterized in that: The molar ratio of the cerium salt to the nickel salt is 1:(0.01-0.3).
5. The preparation method according to claim 1, characterized in that: The alkali is at least one of sodium hydroxide and potassium hydroxide.
6. The preparation method according to claim 1, characterized in that: The total molar ratio of the cerium salt and the nickel salt to the base is 1:(1-100).
7. The preparation method according to claim 1, characterized in that: The method of adding alkali is rapid addition.
8. The preparation method according to claim 1, characterized in that: The hydrothermal treatment temperature is (60-120)°C.
9. The preparation method according to claim 1, characterized in that: The hydrothermal treatment time is (1 to 24) hours.
10. The preparation method according to claim 1, characterized in that: The drying temperature is (30~60)℃.
Citation Information
Patent Citations
Preparation method for nanorod cerium dioxide-nickel oxide composite oxide
CN104841443A
Preparation method of superfine ceric oxide nanowire
CN107814406A
Cerium dioxide fibrous catalyst containing nickel particles and preparation method thereof
CN113351211A
Preparation method of cerium dioxide superfine nanowire
CN116969498A